2006
DOI: 10.1002/eat.20254
|View full text |Cite
|
Sign up to set email alerts
|

Use of diet pills and other dieting aids in a college population with high weight and shape concerns

Abstract: A significant number of college women at risk for eating disorders are using diet aids. We recommend that clinicians inquire about diet aid use among college-aged patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Although the EDE-Q is widely used, 14,15 this is, to our knowledge, the first study to present normative EDE-Q data for undergraduate women in the U.S. Compared with Mond et al's 6 Australian agematched sample, our U.S. sample reported significantly higher scores on the Global, Restraint, and EC subscales.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Although the EDE-Q is widely used, 14,15 this is, to our knowledge, the first study to present normative EDE-Q data for undergraduate women in the U.S. Compared with Mond et al's 6 Australian agematched sample, our U.S. sample reported significantly higher scores on the Global, Restraint, and EC subscales.…”
Section: Resultsmentioning
confidence: 55%
“…Given the prevalence of appearance concerns on college campuses, 14,15 dietary restraint and other compensatory weight control strategies may be more normative in this environment; these compensatory behaviors may be more easily shaped by peers who also might restrict their food intake during communal meals in university dining facilities or who share information about weight control strategies in residence halls. Research by Crandall 17 suggested there were significant social influences to conform to normative levels of binge eating within two sororities on a large university campus.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords Eating disorders; diet pills; weight control behaviors; novelty seeking Abuse of diet pills by individuals with eating disorders is well-documented clinically, with prevalence estimates reported as high as 50% (Celio et al, 2006;Mitchell, Pomeroy, & Huber, 1988;Roerig et al, 2003;Steffen, Roerig, Mitchell, & Crosby, 2006). However, empirical studies of features associated with abuse of diet pills are lacking.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…For example, 72% of college women from six regionally dispersed U.S. campuses reported that “their thighs were too fat,” while only 34% reported that they were happy with their weight (Rozin, Bauer, & Catanese, 2003). Recent prevalence estimates of eating-related behaviors based on college women's self-report suggest that 26% engage in dietary restraint, 21 to 32% binge eat, 9% self-induce vomiting, 6 to 9% misuse laxatives, and 7% misuse diuretics (Celio et al, 2006; Luce, Crowther, & Pole, 2008). The occurrence of CREWS suggests that eating disorders may be prevalent among college-aged women.…”
mentioning
confidence: 99%